2003
DOI: 10.1103/physreve.68.015104
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions towards frequency entrainment in large oscillator lattices

Abstract: We simulate two-dimensional lattices of pulse-coupled oscillators with random natural frequencies, resembling pacemaker cells in the heart. As coupling increases, this system seems to undergo two phase transitions in the thermodynamic limit. First, the largest cluster of frequency entrained oscillators becomes macroscopic. Second, all oscillators frequency entrain, except possibly some isolated ones. Between the two transitions, the system has features indicating self-organized criticality. To our knowledge, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…The node is populated by millions of cells, each a small oscillator with a natural frequency of its own (Ostborn et al, 2003). In the healthy heart these frequencies are phase locked, enabling the node to produce regular contraction commands.…”
Section: Introductionmentioning
confidence: 99%
“…The node is populated by millions of cells, each a small oscillator with a natural frequency of its own (Ostborn et al, 2003). In the healthy heart these frequencies are phase locked, enabling the node to produce regular contraction commands.…”
Section: Introductionmentioning
confidence: 99%
“…When d ജ 2, states with 0 Ͻ r Ͻ 1 are possible and may appear when the natural frequency distribution has tails or the coupling is not strong enough to allow perfect entrainment. There is numerical evidence for such states [11], but analytical results are again lacking. ACKNOWLEDGMENT I thank Bernhard Mehlig, who suggested that I do the present work.…”
Section: Discussionmentioning
confidence: 95%
“…(4)]. In addition, we limited ourselves to coupling functions ⌫͑x͒ fulfilling either case (10) or (11). The last limitation is not essential if we just want to make sure that there is a critical coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theoretical studies on diffusive coupling have appeared in the literature in recent years. Some of them concentrate on mathematical theory (5)(6)(7)(8) and others include physiological aspects (9)(10)(11). Although diffusive coupling is more common and realistic in many physical systems (12)(13)(14), it is neither well understood nor widely studied compared to the global coupling (12,13,15).…”
Section: Introductionmentioning
confidence: 99%